Development of a Rapid Method for the Determination of Phenolic Antioxidants in Dark Chocolate Using Ultra Performance Liquid Chromatography Coupled to Orbitrap Mass Spectrometry. (23rd February 2019) - Rusko, Janis; Pugajeva, Iveta; Perkons, Ingus; Reinholds, Ingars; Bartkiene, Elena; Bartkevics, Vadims
Abstract: Development of a new comprehensive method based on one-step liquid-liquid extraction (LLE) combined with ultra-high-performance liquid chromatography—Orbitrap high resolution mass spectrometry (UHPLC-Orbitrap-HRMS) for the determination of eight phenolic compounds in dark chocolate is demonstrated. The study focuses on the optimization of sample preparation, chromatographic separation and Orbitrap-HRMS detection parameters to adjust selectivity and sensitivity of the method. The LLE mixture of formic acid–water–acetonitrile (2:58:40, v / v ) and hexane at the component ratio of 1:1 ( v / v ) was applied for sample preparation. The inter-day and intra-day precision expressed from the relative standard deviations (RSDs) ranged between 5.50–14.2% and 5.60–16.2%. The quantification limits of the target analytes were between 0.1 and 1.0 mg/kg. The method was applied for the analysis of twenty-six samples of dark chocolate with various cocoa solid contents (30–77%) collected from the markets in Latvia. The total levels of the phenolic contents ranged between 330 and 2631 mg/kg. The study demonstrates advantages of the Orbitrap-HRMS method for the study of phenolic compounds in dark chocolate.